St. James's Hospital and Lucas Engineering Systems Ltd - A public/private sector collaboration in BPR project A - elective admissions - Bence, Valerie (Cranfield School of Management, 1995)
This Working Paper is the first in a series of three examining Business Process Re-design (BPR) within the National Health Service (NHS). This paper, together with Manuscript 13, will examine in detail two BPR projects within a particular NHS hospital and will concentrate on the design and implementation of the projects, the problems encountered and lessons learned. The last in the series (Manuscript 14) will draw on these two examples and similar projects, in order to follow the application of BPR to the NHS and investigate differences and/or similarities in its transfer from private to public sector, in the critical success factors or reasons for failure. It will then attempt to conclude whether the problems, processes and outcomes of using BPR are broadly similar within both public and private sector organisations and thus easily transferable, or if there is in fact a distinction to be made between the two sectors in their approach to and use of BPR as a management tool.